Scenario Building by Design: Pathways Towards Anticipative Collaborative Governance by Design - Corbin Raymond (DIID)
This article explores how design scenarios can support anticipation, collaborative governance, and democratic decision-making across sectors. In focus is the use of scenario building that is communicated through conceptual and process diagrams, as well as contextual situations of people participating with designed artefacts to illustrate how scenario building can encourage community engagement to address challenges like water security and stewardship. By building on established design practices and literature on scenarios in design, the article proposes ‘Anticipative Collaborative Governance’ as a model for creating long-term, systemic solutions through design. It further contributes to cross-sector collaboration by introducing twelve guiding principles to strengthen connections between anticipatory, systemic, and collaborative design.